ALL THE REFORMS ARE FOR HUMAN DIGNITY - Nigina Shoeva (Journal Park Publishing, 2023)
No matter which district of the Surkhandarya region of the Republic of Uzbekistan you go to, the change and renewal there will brighten your heart. In particular, asphalt is being laid on internal streets that are muddy in winter and dusty in summer, and new networks are being laid in places where there is no drinking water. All these works serve the population to live comfortably. After all, it is a fact that problems are solved in front of people's eyes with their participation, construction and repair work, and the continuity of creative work are carried out for the sake of human dignity.